CPAP modulation of sleep microstructure (N2-SSD and REM-AHI) as predictors of neurological recovery in ischemic stroke patients with moderate-to-severe OSA - Jing, Tianyu; Xu, Liwen; Sun, Shutong; Yu, Wenyi; Zheng, Yixi; Xu, Gang; Shen, Xinhao; Tang, Tieyu; Chu, Cheng (Frontiers in Neurology, 2025)
BackgroundThere is a disease spectrum of ischemic stroke (IS) and obstructive sleep apnea (OSA), which are often comorbid in the same patient and consequently increases prognostic risk. Continuous positive airway pressure (CPAP) therapy is the primary treatment for stroke-related OSA; however, its positive effects on patient prognosis and the underlying mechanisms remain controversial.ObjectiveThis study aimed to investigate the impact of CPAP therapy on the recovery of IS patients with moderate-to-severe OSA and to identify biomarkers significantly associated with prognosis to assess their predictive value for short-term neurological outcomes. The findings are expected to optimize treatment strategies and improve overall patient outcomes.MethodsA total of 141 patients with IS combined with moderate-to-severe OSA admitted to the Affiliated Hospital of Yangzhou University from October 2022 to August 2024 were enrolled. Patients were divided into a CPAP group (n = 68) and a control group (n = 73). Both groups received systematic treatment and were followed up until 1 month after the onset of stroke symptoms. The CPAP group initiated therapy within 48 h of stroke onset (ResMed AutoCPAP, pressure 4–20 cmH2O) for 14 days (adherence criterion: ≥4 h/day). Baseline data, sleep and stroke-related questionnaires, polysomnography (PSG) parameters, and sleep spindle characteristics were collected. Neurological functional outcomes were reassessed at the end of the follow-up period, and differences between the two groups were analyzed. Prognostic factors were identified using Spearman correlation analysis and ordered logistic regression.ResultsCompared with those in the control group, patients in the CPAP group had lower modified Rankin scale (mRS) and National Institutes of Health Stroke Scale (NIHSS) scores after treatment (p < 0.05), while the Barthel index (BI) did not significantly differ. Spearman correlation analysis revealed that mRS scores were positively correlated with the apnea-hypopnea index (AHI), the AHI during the rapid eye movement stage (REM-AHI) and the AHI during the non-rapid eye movement stage (NREM-AHI) (all p < 0.05) and negatively correlated with the non-rapid eye movement stage 2 sleep spindle density (N2-SSD), the non-rapid eye movement stage 3 (N3) sleep percentage, and the mean pulse oxygen saturation (Mean SpO2) (all p < 0.05). Logistic regression revealed that N2-SSD, Mean SpO2, and REM-AHI were significant predictors of mRS scores (all p < 0.05).ConclusionCPAP therapy enhances sleep microstructure and oxygenation parameters, which improves sleep quality. N2-SSD, REM-AHI, and Mean SpO2 are mechanistically linked to functional prognosis and CPAP exerts therapeutic effects through the modulation of these biomarkers. Early CPAP intervention targeting REM-AHI and N2-SSD demonstrates prognostic benefits, which suggests that sleep microstructure-specific metrics may serve as precision therapeutic targets.